Application of sustainable agriculture in potato cultivation in highland vegetable farmers, Batu, Malang - Erdiansyah, Iqbal; Angga, septa dwi; Wardani, Faine Arum; Syahida, Ahya Ibadina; Eko Mulyono, Syikril Nur (KHD Production, 2025)
Sustainable agriculture is an agricultural system that considers the environment and the use of natural materials and can make agriculture an organic farming system. This study, which is used as a forum for community service for farmers, aims to determine the response of the application of Lemuru Fish Amino Acid, Sp-36 Application, and Humic Acid to potato yields. This activity began from February to May 2025 in the fields of highland vegetable farmers, Sumber Berantas, Bumiaji, Batu, Malang. The application of Lemuru Fish Amino Acid was carried out using a drip system, using a dose of 30 ml / l, and an interval of 1 week once starting from 21 days after planting (DAP) to 14 days before harvest. The addition of sp-36 fertilizer was given at the beginning only with 6 g / plant sausage by digging, and the application of Humic Acid with a dose of 50 g / l, using two methods if high rainfall was carried out by a sprinkling system and if high rainfall was carried out by a drip system. The parameters observed included the total number of tubers and the total weight of the tubers. The results of this study showed that the application of Lemuru Fish Amino Acid had a very significant effect on production results with results of 6.95 for the total number of tubers, and 83 for the total number of tubers. Thus, the use of organic materials and ecological methods such as this has great potential to support sustainable and productive organic farming.